2019
DOI: 10.3390/molecules24030598
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Thirteen Q-Markers in Raw and Processed Tussilago farfara L. by UPLC-QQQ-MS/MS Coupled with Chemometrics

Abstract: The purpose of this study was to establish a rapid, reliable, and sensitive ultra-performance liquid chromatography with triple-quadrupole tandem mass spectrometry coupled with chemometric method to measure and evaluate the differences between thirteen compounds in raw and processed Tussilago farfara L. from different sources. This assay method was validated, and the results indicated that the calibration curves for the thirteen compounds had good linearity (R2 > 0.9990). The limits of detection and limits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…These three electrodes were connected to a CHI660E electrochemical workstation. The potential scan rate was 3 mV s −1 and the sample exposed area was 1 cm 2 , the rest of the surface were sealed with epoxy resin …”
Section: Methodsmentioning
confidence: 99%
“…These three electrodes were connected to a CHI660E electrochemical workstation. The potential scan rate was 3 mV s −1 and the sample exposed area was 1 cm 2 , the rest of the surface were sealed with epoxy resin …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, rutin ( 64 ) has been identified in the MeOH extract of flower buds of coltsfoot by MS data and comparison of the NMR data analysis ( Gao et al , 2008 ). Kaempferol-3-O-rutinoside ( 70 ) ( Yang et al , 2019 ) and hyperoside ( 63 ) ( Seo et al , 2015 ) have also been identified in flower buds of coltsfoot. The structures ( 58–70) are listed in Fig.…”
Section: Phytochemical Aspectmentioning
confidence: 99%
“…The phenylpropane derivatives and esters of phenylpropanoic acids were separated and purified by different chromatographic methods and their structures were elucidated by IR, MS and 1 H and 13 C NMR data ( Kang et al , 2016 ; Kuroda et al , 2016 ; Li et al , 2018 ; Liu et al , 2007 ; Liu, Y.F. et al , 2007; Wang et al , 2019 ; Yang et al , 2018 ; Yang et al , 2019 ; Zhao et al , 2014 ; Zhi et al , 2012 ). It is worth noting that for exploring the isomers of phenolic acids by UPC 2 is efficient ( Wang et al , 2019 ).…”
Section: Phytochemical Aspectmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) has been used for thousands of years in China. In recent years, TCM has garnered worldwide attention owing to its low toxicity, high efficiency and they are widely grown in many provinces of China, with high yields and no shortage of resources (Wang, Dan, Ming, Ting, & Yin, 2018;Yang et al, 2019). However, the comprehensive quality control of TCM is a complex problem that scholars have not yet overcome.…”
Section: Introductionmentioning
confidence: 99%